A New Software to Model Earth Fissure Caused by Extensive Aquifer Exploitation and its Application to the Guangming Village Case, China - Y. Li; M. Frigo; Y. Zhang; L. Zhu; M. Ferronato; C. Janna; X. Gong; J. Yu; P. Teatini; S. Ye (Proceedings of the International Association of Hydrological Sciences, 2020)
Earth fissures accompanying anthropogenic land subsidence due to excessive aquifer exploitation create significant geohazards in China. Numerical models represent a unique scientific approach to predict the generation and development of earth fissures. However, the common geomechanical simulators fail to reproduce fissure development because they cannot be effectively applied in discontinuous mechanics. An innovative modelling approach developed recently is applied to develop a software to simulate fissure development. The pressure changes are used as forcing factors in a 3D geomechanical model, which combines Finite Elements and Interface Elements to simulate the deformation of the continuous aquifer system and the generation and sliding/opening of earth fissures. The approach has been applied to simulate the earth fissures at Guangming Village in Wuxi, China with land subsidence of more than 1 m caused by the overexploitation of the second confined aquifer. The modelling results highlight that the earth fissures at Guangming Village have been caused by tension and shear stresses. Based on the developed modelling approach and the application case study, a software platform is developed to provide a fast preliminary evaluation of the risk of fissure occurrence associated to land subsidence. The software allows for the simulation of a simplified 2D conceptual geologic model of earth fissures, which can be used to investigate how the main factors controlling the geomechanical response of the aquifer system, such as pressure changes, geometry of aquifer system, geomechanical properties, and depth of bedrock/fault etc.